2013
DOI: 10.1016/j.vetpar.2012.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Pro-inflammatory cytokines predominate in the brains of dogs with visceral leishmaniasis: A natural model of neuroinflammation during systemic parasitic infection

Abstract: Visceral leishmaniasis is a multisystemic zoonotic disease that can manifest with several symptoms, including neurological disorders. To investigate the pathogenesis of brain alterations occurring during visceral leishmaniasis infection, the expression of the cytokines IL-1β, IL-6, IL-10, IL-12p40, IFN-γ, TGF-β and TNF-α and their correlations with peripheral parasite load were evaluated in the brains of dogs naturally infected with Leishmania infantum. IL-1β, IFN-γ and TNF-α were noticeably up-regulated, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 85 publications
4
35
0
Order By: Relevance
“…Other groups have investigated the cytokine profiles present in other tissues such as the brain, jejunum and colon that were deemed less commonly associated with L. infantum infection in dogs (Figueiredo et al 2013; Melo et al 2013). Figueiredo et al .…”
Section: Organ Specific Immune Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other groups have investigated the cytokine profiles present in other tissues such as the brain, jejunum and colon that were deemed less commonly associated with L. infantum infection in dogs (Figueiredo et al 2013; Melo et al 2013). Figueiredo et al .…”
Section: Organ Specific Immune Responsesmentioning
confidence: 99%
“…reported higher levels of IL-10 and TNF- α in the jejunum than the colon of infected animals, whereas IL-4 was higher in the colon than the jejunum of infected animals (Figueiredo et al 2013). In the brains of CanL dogs, Melo et al reported that IL-10, TGF- β and IL-12p40 were downregulated, while IL-1- β , IFN- γ and TNF- α were upregulated, however expression levels did not correlate with parasite load (Melo et al 2013). The authors suggested that the differences seen in the brain were due to the host's immune response, regardless of the phase of the disease (Melo et al 2013).…”
Section: Organ Specific Immune Responsesmentioning
confidence: 99%
“…A decreased liver function would result in increased activities of ALT and AST, characterizing liver injury [33]. In this sense, it is necessary to consider that, VL affects mainly the organs with cells of the mononuclear phagocyte system, such as the spleen, lymph nodes, bone marrow and liver [2]. The typical histopathological finding is a granulomatous inflammatory reaction associated with presence of Leishmania amastigotes, within macrophages [1].…”
Section: Variablesmentioning
confidence: 99%
“…Leishmaniasis is transmitted by over 30 distinct phlebotomine sand flies, and it has four different types of clinical presentation: visceral leishmaniasis (VL), cutaneous leishmaniasis, muco-cutaneous leishmaniasis, and post-kala-azar dermal leishmaniasis (PKDL) [1,2]. VL, also known as kala-azar, is an anthropozoonosis caused by Leishmania donovani complex: Leishmania infantum (Syn.…”
Section: Introductionmentioning
confidence: 99%
“…A syndrome characterized by abnormal behaviours and believed to be consequence of such neurodegeneration has been described in aged dogs [15]. Dogs have also been proposed as models for other neurological diseases, including epilepsy as well as neurodegenerative and inflammatory neurological conditions [2,11,14], in which a role of cortisol, DHEA and DHEA-S could be hypothesized. The study of DHEA and cortisol in the pathophysiology of canine CNS is therefore relevant to both veterinary and human medicines.…”
mentioning
confidence: 99%